1
1
mirror of https://github.com/thma/WhyHaskellMatters.git synced 2024-11-22 20:35:15 +03:00
WhyHaskellMatters/functor-proof.md

96 lines
2.8 KiB
Markdown
Raw Normal View History

2020-04-16 13:41:05 +03:00
# Proof of functor laws for Maybe
2020-04-17 17:37:03 +03:00
In this section I want to give a short example of how equational reasoning can be used to
proof certain properties of a given piece of code in Haskell.
2020-04-16 13:41:05 +03:00
2020-04-17 17:37:03 +03:00
So without further ado let's begin:
## Known facts
The `Functor` instance declaration of the type `Maybe` is defined as:
2020-04-16 13:41:05 +03:00
```haskell
instance Functor Maybe where
fmap _ Nothing = Nothing -- (1)
fmap f (Just a) = Just (f a) -- (2)
```
2020-04-17 17:37:03 +03:00
The composition operator `(.)` is defined as:
2020-04-16 13:41:05 +03:00
```haskell
(.) :: (b -> c) -> (a -> b) -> a -> c
2020-04-17 17:37:03 +03:00
f . g x = f (g x) -- (3)
2020-04-16 13:41:05 +03:00
```
2020-04-17 17:37:03 +03:00
The Identity function `id` is defined as:
2020-04-16 13:41:05 +03:00
```haskell
id :: a -> a
2020-04-17 17:37:03 +03:00
id x = x -- (4)
2020-04-16 13:41:05 +03:00
```
2020-04-17 17:37:03 +03:00
## Claim
2020-04-16 13:41:05 +03:00
2020-04-17 17:37:03 +03:00
The claim is that `Maybe` fulfils the two functor laws:
2020-04-16 13:41:05 +03:00
```haskell
1.: fmap id = id
2.: fmap (f . g) = (fmap f . fmap g)
```
## Proof of the first law
**Claim:** `fmap id m = id m`, for any `m` of type `Maybe a`.
**Proof.** On cases of `m`.
*Case 1:* `m = Nothing`.
```haskell
fmap id m = fmap id Nothing -- by expansion of m
= Nothing -- by applying equation (1)
= id m -- by definition m, by applying equation (4)
```
*Case 2:* `m = Just a`.
```haskell
fmap id m = fmap id (Just a) -- by expansion of m
= Just (id a) -- by applying equation (2)
= Just a -- by expansion of id (equation (4))
= m -- by definition of m
= id m -- by applying equation (4)
```
Therefore, `fmap id m = id m` in all cases.∎
## Proof of the second law
**Claim:** `fmap (f . g) m = (fmap f . fmap g) m`, for any `m` of type `Maybe a`.
**Proof.** On cases of `m`.
*Case 1:* `m = Nothing`.
```haskell
fmap (f . g) m = fmap (f . g) Nothing -- by expansion of m
= Nothing -- by applying equation (1)
2020-04-17 17:37:03 +03:00
(fmap f . fmap g) m = fmap f (fmap g Nothing) -- by applying equation (4) and expanding m
2020-04-16 13:41:05 +03:00
= fmap f Nothing -- by applying equation (1)
= Nothing -- by applying equation (1)
```
*Case 2:* `m = Just a`.
```haskell
fmap (f . g) m = fmap (f . g) (Just a) -- by expansion of m
= Just ((f . g) a) -- by applying equation (2)
2020-04-17 17:37:03 +03:00
(fmap f . fmap g) m = fmap f (fmap g (Just a)) -- by applying equation (4) and expanding m
2020-04-16 13:41:05 +03:00
= fmap f (Just (g a)) -- by applying equation (2)
= Just (f (g a) -- by applying equation (2)
= Just ((f . g) a) -- by applying equation (3)
```
Therefore, `fmap (f . g) m = (fmap f . fmap g) m` in all cases. ∎
2020-04-17 17:37:03 +03:00
## Conclusion
You'll see this kind of reasoning quite a lot in Haskell documentation and online discussions.
The simple reason is: if you can prove something you don't have to test it.